Use of a combination of ketamine and dexmedetomidine (Ketodex) in different clinical cases - Somchai Amornyotin (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Ketodex is a combination of ketamine and dexmedetomidine. Ketamine, an old intravenous anesthetic, is a non-narcotic and non-barbiturate drug. It has several properties of the ideal anesthetic agent. However, ketamine can produce the psychological adverse effects. Dexmedetomidine has analgesic, amnesic, sedative and anxiolytic properties. A distinct advantage of dexmedetomidine is the maintenance of respiratory force and preserved airway patency. It converges on a natural sleep pathway, activating pathways that promote endogenous non-rapid eye movement sleep to exert its sedative effect. However, dexmedetomidine can produce bradycardia and hypotension. A combination of ketamine and dexmedetomidine has several benefits in the terms of hemodynamic stability, absence of respiratory depression, post-operative analgesia and recovery. Several previous studies have been demonstrated the therapeutic utility of the combination of ketamine and dexmedetomidine.